2021
DOI: 10.1038/s41598-021-87327-3
|View full text |Cite
|
Sign up to set email alerts
|

Using mounting, orientation, and design to improve bat box thermodynamics in a northern temperate environment

Abstract: Wildlife managers design artificial structures, such as bird houses and bat boxes, to provide alternative nesting and roosting sites that aid wildlife conservation. However, artificial structures for wildlife may not be equally efficient at all sites due to varying climate or habitat characteristics influencing thermal properties. For example, bat boxes are a popular measure employed to provide compensatory or supplementary roost sites for bats and educate the public. Yet, bat boxes are often thermally unstabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Yet, this temperature effect still ought to be demonstrated for snowfinch nest sites as we did not measure microclimate inside the nest cavities. Especially, it remains unclear if the temperature effect would hold true for all types of nests (rocks, pylons and buildings) as the temperature inertia might vary considerably among them (Grüebler et al 2014, Maziarz et al 2017, Larson et al 2018, Fontaine et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, this temperature effect still ought to be demonstrated for snowfinch nest sites as we did not measure microclimate inside the nest cavities. Especially, it remains unclear if the temperature effect would hold true for all types of nests (rocks, pylons and buildings) as the temperature inertia might vary considerably among them (Grüebler et al 2014, Maziarz et al 2017, Larson et al 2018, Fontaine et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, our findings strongly support the idea that nest box design, material, and positioning can be key factors in determining the effectiveness of conservation interventions and in improving the resilience of target species in the face of rapidly changing climatic conditions (Catry et al, 2011). More broadly, incorporating energy‐saving concepts from architecture in the design of wildlife‐dedicated structures can considerably improve their thermal performance and hence the success of conservation efforts under global warming scenarios (Fontaine et al, 2021). In urban settings, integrating such structures with innovative and biodiversity‐friendly architectural solutions (such as green roofs; Fernández Cañero & González Redondo, 2010) could further boost their ecological and conservation value.…”
Section: Discussionmentioning
confidence: 99%
“…This will allow for active roost selection by bats (Kerth et al, 2001;Ruczyński, 2006) and roost switching when necessary (Ellison et al, 2007;Patriquin et al, 2016). This variation is critical to ensure there are suitable microclimates for individuals during post-hibernation or migration, for maternity colonies, and to prevent them from becoming death traps during heat waves (Bideguren et al, 2019;Flaquer et al, 2014;Fontaine et al, 2021;Griffiths, 2021). These recommendations are of particular importance to conservation managers in the hotter and dryer regions of these species' range where heat-related mortality is already being observed (Alcalde et al, 2017;Flaquer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, bat boxes can become hotter than natural roosts, sometimes exceeding normothermic T b (Bideguren et al, 2019;Crawford & O'Keefe, 2021;Flaquer et al, 2014;Lourenço & Palmeirim, 2004), and individuals have been observed abandoning boxes at T roost > 40°C (Flaquer et al, 2014;Lourenço & Palmeirim, 2004). Several recent studies warn that bat boxes are at risk of overheating and that this conservation practice may be an ecological trap for bats (Crawford & O'Keefe, 2021;Crawford et al, 2022;Flaquer et al, 2014;Fontaine et al, 2021;Griffiths, 2021); however, none have measured the heat tolerance or evaporative water requirements of their occupants to quantify that risk.…”
Section: Introductionmentioning
confidence: 99%